Foamed ceramic derived from all solid wastes and preparation method thereof

By preparing foam ceramics from Dexing copper mine tailings, electrolytic manganese slag and fly ash, the problem of industrial solid waste accumulation and pollution has been solved, and efficient solid waste resource utilization and excellent ceramic properties have been achieved.

CN119330742APending Publication Date: 2025-01-21SHANGRAO NORMAL UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411629997.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The accumulation of industrial solid waste leads to land occupation and environmental pollution, and the existing technology is difficult to effectively utilize Dexing copper mine tailings, electrolytic manganese slag and fly ash.

Method used

The use of Dexing copper ore tailings, electrolytic manganese residue, and flour ash as raw materials, prepare foam ceramics derived from the foothills derived from the foam, drying, mixed organic adhesives, pressing for molding, and high -temperature sintering.

Benefits of technology

Successfully prepared all-solid waste foam ceramics with excellent comprehensive properties, with a volume density of 0.30-0.81g/cm3, a porosity of 64.52-91.92%, and a compressive strength of 0.41-3.35MPa, while ensuring 100% industrial solid waste utilization of raw materials .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330742A_ABST
    Figure CN119330742A_ABST
Patent Text Reader

Abstract

The invention discloses full solid waste derived foamed ceramic and a preparation method thereof, the selected raw materials comprise 60-69% by mass of Dexing copper mine tailings, 7-8% by mass of electrolytic manganese residues and 23-33% by mass of fly ash. The preparation method comprises the following steps: ball-milling and drying the three raw materials, and uniformly mixing the three raw materials with an organic binder (7wt% polyvinyl alcohol solution) accounting for 5% of the total mass of the raw materials in a ceramic mortar according to a designed mass ratio to obtain a batch; then putting the mixture into a metal mold, and pressing the mixture into a precursor under the pressure of 20MPa by using a small-sized manual sample press; and sintering the precursor in a high-temperature muffle furnace at the temperature of between 1,160 and 1,220 DEG C for 1 hour, and cooling along with the furnace to obtain the foamed ceramic. The raw materials of the foamed ceramic are all from industrial solid wastes, and the synthesized foamed ceramic has excellent properties such as light weight (volume density of 0.30-0.81 g / cm < 3 >), high porosity (64.52-91.92%), high compression strength (0.41-3.35 MPa) and the like, and has a wide application prospect in the fields of building walls and heat-insulating fireproof materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the utilization of industrial solid waste, and in particular to a method for preparing foam ceramics by using Dexing copper mine tailings / electrolytic manganese slag / fly ash as raw materials. Background Art

[0002] The accumulation of industrial solid waste has become a serious environmental problem, with a total annual amount of 500 million tons and a cumulative amount of 60 billion tons, occupying more than 2 million hectares of land. Due to technical and cost limitations, most industrial solid waste can only be handled by simple methods such as landfill or stockpiling, which not only consumes a lot of land resources, but also because of the wide variety and complex composition of industrial solid waste, it is easily affected by environmental factors and produces secondary pollution, threatening human health and the ecological environment. Therefore, realizing the resource utilization of industrial solid waste and reducing land occupation and environmental pollution has significant social and ecological benefits.

[0003] As the largest associated gold and silver mine in China, Dexing Copper Mine has accumulated a large amount of difficult-to-handle tailings after long-term mining. The amount of tailings has continued to grow from about 220 million tons in 2000 to 300 million tons in 2010, and then to 500 million tons in 2020, and is still increasing. At present, tailings treatment mainly relies on tailings pond storage, lacking effective comprehensive utilization methods. If the tailings pond leaks, dams burst or other problems occur, it will have a long-term and irreversible serious impact on the surrounding natural ecological environment. Therefore, it is particularly urgent to explore efficient resource utilization methods for Dexing Copper Mine tailings.

[0004] In the process of preparing electrolytic manganese, a huge amount of electrolytic manganese slag will be produced. At present, most electrolytic manganese enterprises simply pile up the electrolytic manganese slag by requisitioning land. However, given that the chemical composition of electrolytic manganese slag contains toxic and harmful substances, it will seriously pollute the environment. Fly ash, as a fine solid particle captured in the flue gas generated in the coal combustion process, is one of the main industrial solid wastes with a large output in my country. Every year, more than 100 million tons of fly ash are piled up and stored because they cannot be effectively utilized, which not only occupies a large amount of land resources, but also brings a series of environmental problems and safety hazards. Therefore, how to harmlessly treat electrolytic manganese slag and fly ash is also one of the major problems that the current society urgently needs to solve.

[0005] As a new type of building material, foam ceramics have shown great application prospects in the fields of building walls and thermal insulation and fireproof materials due to their excellent high-temperature stability, sound insulation, heat insulation, and excellent earthquake resistance. In the study of solid waste resource utilization of copper mine tailings, electrolytic manganese slag or fly ash, Chinese patent application number CN201210446992.1 discloses a porous ceramic material of copper mine tailings and its preparation method. In addition to copper mine tailings, the raw materials also include porogens (5-45%), binders (1-35%) and fluxes (1-10%). This method has many types of raw materials and a complex heat treatment system. Porogens, binders and fluxes are added during the preparation process, and the utilization rate of copper mine tailings is not high. It does not involve the preparation of materials using all solid waste as raw materials, nor does it involve the utilization of electrolytic manganese slag or fly ash.

[0006] Chinese patent application number CN202311828889.8 discloses a composite pore-forming agent composed of electrolytic manganese slag, graphite tailings, and silicon carbide powder and a method for preparing microcrystalline foamed ceramics. Aluminosilicate industrial solid waste and 3-15% refractory brick waste are used as foam stabilizers, electrolytic manganese slag, graphite tailings, and a composite pore-forming agent composed of silicon carbide powder, and 0.1-0.5% triethanolamine are used to prepare microcrystalline foamed ceramics, and the amount of electrolytic manganese slag (mass percentage) is 2-10%. This method has many types of raw materials for preparing foamed ceramics, and a certain amount of pore-forming agent needs to be added, and it does not involve the use of copper mine tailings or fly ash.

[0007] Chinese patent application number CN202311023949.9 discloses a high-strength foam ceramic and a preparation method thereof. Raw materials with a mass ratio of titanium slag: fly ash = 30-40: 60-70 or titanium slag: fly ash: asbestos tailings = 30-40: 30-60: 0-40 are ball-milled to obtain a green body powder, and the green body powder is granulated, dried and aged to obtain green body powder particles. The obtained green body powder particles are pressed and dried to obtain a green body, and then sintered at high temperature to obtain foam ceramics. The preparation process of this preparation method is relatively complicated and requires multiple steps. Summary of the invention

[0008] The invention provides a foam ceramic completely derived from industrial solid waste and a preparation method thereof. The industrial solid waste used includes: Dexing copper mine tailings, electrolytic manganese slag and fly ash.

[0009] The object of the present invention is achieved by: A foam ceramic derived from solid waste and a preparation method thereof, characterized in that the steps are as follows:

[0010] 1) After ball milling and drying, the particle size of Dexing copper mine tailings, electrolytic manganese slag and fly ash is ≥200 mesh;

[0011] 2) According to the preset mass ratio, mix evenly with 5% of the total mass of the raw materials with an organic binder (7wt% polyvinyl alcohol solution) in a ceramic mortar to obtain a batch material. The raw material ratio is as follows: 60-69% of Dexing copper mine tailings, 7-8% of electrolytic manganese slag, and 23-33% of fly ash;

[0012] 3) The batch material is loaded into a metal mold and pressed at a pressure of 20 MPa using a small manual press to obtain a foam ceramic precursor;

[0013] 4) The precursor is placed in a high-temperature muffle furnace, heated to 1160-1220°C at a rate of 5°C / min, kept at this temperature for 1 hour, and cooled with the furnace to obtain foam ceramics. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is a physical picture of the foam ceramic prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0015] The present invention is further described below with reference to the embodiments, but the protection scope of the present invention should not be limited thereto.

[0016] A foam ceramic derived from solid waste and a preparation method thereof, wherein the steps are as follows:

[0017] 1) After ball milling and drying, the particle size of Dexing copper mine tailings, electrolytic manganese slag and fly ash is ≥200 mesh;

[0018] 2) According to the preset mass ratio, 5% of the total mass of the raw materials and an organic binder (7wt% polyvinyl alcohol solution) are mixed evenly in a ceramic mortar to obtain a batch material. The raw material ratio is as follows: 60-69% of Dexing copper mine tailings, 7-8% of electrolytic manganese slag, and 23-33% of fly ash. During the mixing stage with the raw material particles, the binder can provide bonding force between the raw material particles, which is beneficial for the raw material particles to form a precursor under the action of a small prototyping machine. In addition, during the high-temperature sintering stage, the binder is decomposed by high temperature to ensure that the foam ceramic raw material is 100% industrial solid waste;

[0019] 3) The batch material is loaded into a metal mold and pressed at a pressure of 20 MPa using a small manual press to obtain a foam ceramic precursor;

[0020] 4) The precursor is placed in a high-temperature muffle furnace, heated to 1160-1220°C at a rate of 5°C / min, kept at this temperature for 1 hour, and cooled with the furnace to obtain foam ceramics.

[0021] Embodiment 1:

[0022] After the Dexing copper mine tailings / electrolytic manganese slag / fly ash are ball-milled and dried completely, they are accurately weighed according to the mass percentage of 69 / 8 / 23%, mixed evenly with a binder accounting for 5% of the total mass of the raw materials in a ceramic mortar, and then transferred into a metal mold and pressed into a foam ceramic precursor under a pressure of 20MPa on a small manual press. The precursor is placed in a high-temperature muffle furnace and heated to 1160℃ at a uniform rate of 5℃ / min and kept warm for 1 hour. After cooling with the furnace, foam ceramics are obtained, and its volume density is 0.52g / cm 3 , porosity is 69.90%, compression strength is 1.83MPa (see Figure 1 shown).

[0023] Embodiment 2:

[0024] After the Dexing copper mine tailings / electrolytic manganese slag / fly ash are ball-milled and dried completely, they are accurately weighed according to the mass percentage of 69 / 8 / 23%, mixed evenly with a binder accounting for 5% of the total mass of the raw materials in a ceramic mortar, and then transferred into a metal mold and pressed into a foam ceramic precursor under a pressure of 20MPa on a small manual press. The precursor is placed in a high-temperature muffle furnace and heated to 1180℃ at a uniform rate of 5℃ / min and kept warm for 1 hour. After cooling with the furnace, foam ceramics are obtained, and its volume density is 0.33g / cm 3 , the porosity is 91.92% and the compressive strength is 0.52MPa.

[0025] Embodiment 3:

[0026] After the Dexing copper mine tailings / electrolytic manganese slag / fly ash are ball-milled and dried completely, they are accurately weighed according to the mass percentage of 69 / 8 / 23%, mixed evenly with a binder accounting for 5% of the total mass of the raw materials in a ceramic mortar, and then transferred into a metal mold and pressed into a foam ceramic precursor under a pressure of 20MPa on a small manual press. The precursor is placed in a high-temperature muffle furnace and heated to 1200℃ at a uniform rate of 5℃ / min, and kept warm for 1 hour. After cooling with the furnace, foam ceramics are obtained, and its volume density is 0.81g / cm 3 , the porosity is 64.52% and the compressive strength is 2.27MPa.

[0027] Embodiment 4:

[0028] After the Dexing copper mine tailings / electrolytic manganese slag / fly ash are ball-milled and dried completely, they are accurately weighed according to the mass percentage of 60 / 7 / 33%, mixed evenly with a binder accounting for 5% of the total mass of the raw materials in a ceramic mortar, and then transferred into a metal mold and pressed into a foam ceramic precursor under a pressure of 20MPa on a small manual press. The precursor is placed in a high-temperature muffle furnace and heated to 1180℃ at a uniform rate of 5℃ / min and kept warm for 1 hour. After cooling with the furnace, foam ceramics are obtained, and its volume density is 0.55g / cm3 , the porosity is 69.11% and the compressive strength is 3.35MPa.

[0029] Embodiment 5:

[0030] After the Dexing copper mine tailings / electrolytic manganese slag / fly ash are ball-milled and dried completely, they are accurately weighed according to the mass percentage of 60 / 7 / 33%, mixed evenly with a binder accounting for 5% of the total mass of the raw materials in a ceramic mortar, and then transferred into a metal mold and pressed into a foam ceramic precursor under a pressure of 20MPa on a small manual press. The precursor is placed in a high-temperature muffle furnace and heated to 1200℃ at a uniform rate of 5℃ / min, and kept warm for 1 hour. After cooling with the furnace, foam ceramics are obtained, and its volume density is 0.39g / cm 3 , the porosity is 80.66% and the compressive strength is 1.70MPa.

[0031] Embodiment 6:

[0032] After the Dexing copper mine tailings / electrolytic manganese slag / fly ash are ball-milled and dried completely, they are accurately weighed according to the mass percentage of 60 / 7 / 33%, mixed evenly with a binder accounting for 5% of the total mass of the raw materials in a ceramic mortar, and then transferred into a metal mold and pressed into a foam ceramic precursor under a pressure of 20MPa on a small manual press. The precursor is placed in a high-temperature muffle furnace and heated to 1220℃ at a uniform rate of 5℃ / min and kept warm for 1 hour. After cooling with the furnace, foam ceramics are obtained, and its volume density is 0.30g / cm 3 , the porosity is 85.77% and the compressive strength is 0.41MPa.

[0033] The block density in all examples is measured according to GB / T 3810.3-2006 “Test methods for ceramic tiles Part 3 Determination of water absorption, apparent porosity, apparent relative density and bulk density”.

[0034] The porosity in all examples is measured according to GB / T 5071-2013 “Test method for true density of refractory materials”.

[0035] The flexural strength of the samples in all the examples was measured according to GB / T 1965-1996 “Test method for flexural strength of porous ceramics”.

[0036] Table 1 Performance parameters of foam ceramics prepared in Examples 1-6

[0037]

[0038] In the foam ceramics prepared by the present invention, SiO2 and Al2O3 in the raw material composition can construct the foam ceramic skeleton structure; a certain amount of alkali / alkaline earth metal oxides (such as K2O, Na2O, CaO) can be used as sintering aids, and react with SiO2 and Al2O3 to generate a glass phase, thereby forming the pore walls of the foam ceramics; other chemical components (such as Fe2O3) can be used as foaming agents to create a porous structure for the foam ceramics.

[0039] The all-solid waste derived foam ceramic and the preparation method thereof described in the present invention also include the following preferred embodiments:

[0040] In a preferred embodiment, the ideal sintering temperature range of the foam ceramic is 1160-1220°C.

[0041] In the preferred solution, the addition of the binder is conducive to the pressing and molding of the foam ceramic precursor under the action of the prototype press, and the binder is completely decomposed during the subsequent high-temperature sintering, ensuring that the foam ceramic raw material is 100% industrial solid waste.

[0042] In summary, the technical advantages of the present invention bring particularly excellent technical effects:

[0043] 1) Successfully prepared a foam ceramic product from a full solid waste system;

[0044] 2) Low preparation cost, simple and efficient preparation process;

[0045] 3) The prepared foam ceramics have excellent comprehensive performance, which is specifically reflected in: the volume density is 0.30-0.81g / cm 3 , the porosity is 64.52-91.92%, and the compression strength is 0.41-3.35MPa.

Claims

1. A foam ceramic derived from solid waste and a preparation method thereof, the characteristics and steps of which are as follows: 1) After ball milling and drying, the particle size of Dexing copper mine tailings, electrolytic manganese slag and fly ash is ≥200 mesh; 2) According to the preset mass ratio, mix evenly with 5% of the total mass of the raw materials with an organic binder (7wt% polyvinyl alcohol solution) in a ceramic mortar to obtain a batch material. The raw material ratio is as follows: 60-69% of Dexing copper mine tailings, 7-8% of electrolytic manganese slag, and 23-33% of fly ash; 3) The batch material is loaded into a metal mold and pressed at a pressure of 20 MPa using a small manual press to obtain a foam ceramic precursor; 4) The precursor is placed in a high-temperature muffle furnace, heated to 1160-1220°C at a rate of 5°C / min, kept at this temperature for 1 hour, and cooled with the furnace to obtain foam ceramics.

2. The all-solid waste derived foam ceramic and the preparation method thereof according to claim 1, characterized in that: The raw materials used are all industrial solid waste, with a utilization rate of 100%.

3. The all-solid waste derived foam ceramic and the preparation method thereof according to claim 2, characterized in that: The sintering temperature of the foam ceramic is in the range of 1160-1220°C.

Citation Information

Patent Citations

  • Copper mine tailing slag porous ceramic material and preparation method thereof

    CN102924113A

  • Foamed ceramic prepared from fly ash and metallurgical waste residues and preparation method of foamed ceramic

    CN113480324A

  • Mixture for manufacturing of porous ceramics

    RU2379256C1